Aesthetics of Affliction - Guevara, Alberto; Nouvet, Elysée (InTensions, 2008)
In making Aesthetics of Affliction our theme for this first issue, our goal was to engage immediately with questions that must remain central in a journal dealing with corpo-realities of structural violence, the senses, and the theatricality of power. These questions are: how can we talk to experiences and situations that evade translation and that are mired with legacies of objectification? What are the possibilities, limits, hopes, and risks when addressing non-linear moves of power, the work of violence, and social yet also intensely subjective effects/affects?